Study on electrical transport characteristics of aluminum-doped ZnO ceramics under high pressure - Ranjun Zhang; Lijuan Wang; Zeshan Liu; Xin Fan; Fangbiao Wang (Next Materials)
This study utilized ZnO powder and Al powder as raw materials. By varying the temperature using high-pressure methods, we successfully prepared aluminum-doped zinc oxide composite ceramics with excellent electrical conductivity. Characterization using XRD, SEM, Hall experiment, Seebeck test, UV spectroscopy, Raman spectroscopy, and EDS investigated the effects of different high-pressure temperatures on the structure, microstructure, and electrical properties of Al-doped ZnO ceramics. Experimental results indicate that Al did not enter the ZnO lattice but formed a solid solution on the zinc oxide, thereby improving the ceramic's electrical transport properties. These methods collectively produced aluminum-doped zinc oxide-based ceramics with good electrical transport properties. At a sintering temperature of 950 K, the ceramics exhibited a dense structure and excellent electrical properties, achieving a relative density of 97.8 %, electrical conductivity as high as 2.5×106 S/m, and enhanced carrier concentration and power factor, with maxima of n=3.6×1019 cm−3 and Pf = 82.7 μW·cm-1·K−2, respectively.